x=1
x=0,5
Объяснение:
2x^2+x-1=4x-2
2x^2+x-4x-1+2=0
2x^2-3x+1=o
D=3^2-4*2*1=9-8=1
x1=3+1/2*2=4/4=1
x2=3-1/2*2=2/4=1/2=0,5
2х^2+х-1= 4x-2
2x^2+x-1-(4x-2)=4x-2-(4x-2)
2x^2+x-1-(4x-2)=0
2x^2+x-1+((-1)*4x+(-2)(-1))=0
2x^2+x-1+((-4)x+(-2)(-1))=0
2x^2+x-1+((-4)x+2)=0
2x^2+x-1+(-4)x+2=0
2x^2+x+1+(-4)x=0
2x^2+(-3)x+1=0
2x^2+(-3)x+1-1=-1
2x^2+(-3)x=-1
2x^2+(-3)x/2=-1/2
x^2+-3/2x=-1/2
x^2+(-3/2)x=-1/2
x^2+(=3/2)x+(-3/4)^2=-1/2+(-3/4)^2
x^2+(-3/2)x+9/16=1/16
(x-3/4)^2=-1/16
x-3/4=1/4
x-3/4=-1/4
ответ: x=1/2=0.5
x=1
x=0,5
Объяснение:
2x^2+x-1=4x-2
2x^2+x-4x-1+2=0
2x^2-3x+1=o
D=3^2-4*2*1=9-8=1
x1=3+1/2*2=4/4=1
x2=3-1/2*2=2/4=1/2=0,5
2х^2+х-1= 4x-2
2x^2+x-1-(4x-2)=4x-2-(4x-2)
2x^2+x-1-(4x-2)=0
2x^2+x-1+((-1)*4x+(-2)(-1))=0
2x^2+x-1+((-4)x+(-2)(-1))=0
2x^2+x-1+((-4)x+2)=0
2x^2+x-1+(-4)x+2=0
2x^2+x+1+(-4)x=0
2x^2+(-3)x+1=0
2x^2+(-3)x+1-1=-1
2x^2+(-3)x=-1
2x^2+(-3)x/2=-1/2
x^2+-3/2x=-1/2
x^2+(-3/2)x=-1/2
x^2+(-3/2)x=-1/2
x^2+(=3/2)x+(-3/4)^2=-1/2+(-3/4)^2
x^2+(-3/2)x+9/16=1/16
(x-3/4)^2=-1/16
x-3/4=1/4
x-3/4=-1/4
x=1
ответ: x=1/2=0.5